Development of a Phase Field Tool Coupling With Thermodynamic Data for Microstructure Evolution Simulation of Alloys in Nuclear Reactors - Guo, Yaolin; Li, Yifan; Liu, Zhen; Shi, Diwei; Song, Jiexi; Zhang, Biao; Bu, Moran; Du, Shiyu (Frontiers in Materials, 2021)
The development of materials for the accident tolerant fuel systems strongly links to nuclear energy safety and the Material Genome Initiative (MGI) is one of the most promising means to accelerate this process. In the framework of MGI, it is core demand to implement high-throughput and multi-scale simulations, in which the phase-field method plays an important role. Unfortunately, it is not always efficient for phase-field modelling to incorporate thermodynamic information, which hinders its extensive application in MGI. In this article, we develop a software tool in our own phase-field program to automatically incorporate the standard CALPHAD files suffixed with “TDB”, which are supported by the majority of CALPHAD software. The free energy and diffusion potential are established and interpolated based on the extracted parameters through compound-energy formalism by the software tool. As the component of ATF cladding material candidate FeCrAl, the Fe-Cr binary system is taken as an example to show the function of our phase-field program, in which spinodal decomposition is reproduced via WBM model and solid-liquid transition is realized via the KKS model. Our software tools may provide a new solution for the high-throughput phase-field simulation in the multi-scale calculation of MGI.